Pelatihan hygiene sanitasi dan poster berpengaruh terhadap pengetahuan, perilaku penjamah makanan, dan kelaiakan hygiene sanitasi di instalasi gizi RSUP Sanglah Denpasar - Ni Wayan Rapiasih; Yeni Prawiningdyah; Lily Arsanti Lestari (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2010)
Background: The problem of food hygiene sanitation in hospital is closely related to the incidence of nosocomial infection which is estimated to be high considering that the condition of hospitals and health in general is still relatively not very good. A way to transmit nosocomial infection is through food. Staff hygiene is a factor requiring attention in order that the product of nutrition installation is of quality and safe to consume.Objective: To identify the effect of training and posting of food hygiene sanitation to knowledge, healthy behavior of food handlers in efforts to improve food safety and sanitation hygiene appropriateness.Method: This was a time series quasi experiment with one group pre test and post test design. Samples consisted of 44 people of senior level education in charge of food service to patient in class I, II, and III. Every subject was given training using lecture, discussion and demonstration method for one day. Poster was posted a month after training. Data obtained consisted of sex, age, marital status, duration of occupation, place of work, knowledge, behavior, food safety in food serving utensil for inpatients and sanitation hygiene appropriateness. Assessment was made before, one month and two months after training. Data analysis used paired Sample t-test and chi-square.Results: There was signifcant improvement in knowledge and healthy behavior before and after training plus poster showed with p<0.001. There was signifcant difference in sex and behavior before training with p=0.045 and a month after training with p<0.001. There was signifcant association between place of work and behavior a month after training with p=0.021. There was signifcant difference in total plate count one month and two months after training with p=0.049. In addition, there was an increased quality of sanitation hygiene appropriateness before and after training plus poster showed.Conclusion: There was an increasing of knowledge, behavior of food handlers, sanitation hygiene appropriateness, before and after training plus poster. There was an improvement in quality food safety one and two months after training.